NMR structure and MD simulations of the AAA protease intermembrane space domain indicates peripheral membrane localization within the hexaoligomer. Issue 21 (18th September 2013) - Ramelot, Theresa A.; Yang, Yunhuang; Sahu, Indra D.; Lee, Hsiau-Wei; Xiao, Rong; Lorigan, Gary A.; Montelione, Gaetano T.; Kennedy, Michael A.
Abstract : We have determined the solution NMR structure of the intermembrane space domain (IMSD) of the human mitochondrial ATPase associated with various activities (AAA) protease known as AFG3‐like protein 2 (AFG3L2). Our structural analysis and molecular dynamics results indicate that the IMSD is peripherally bound to the membrane surface. This is a modification to the location of the six IMSDs in a model of the full length yeast hexaoligomeric homolog of AFG3L2 determined at low resolution by electron cryomicroscopy [1]. The predicted protein–protein interaction surface, located on the side furthest from the membrane, may mediate binding to substrates as well as prohibitins. Abstract : The first atomic‐resolution structure of the IMSD of a m ‐AAA protease is presented. MD simulations reveal the peripheral membrane interaction of the IMSD. We model the location of the six IMSDs in the full‐length AFG3L2 hexaoligomer.